The Routledge Handbook of Anarchy and Anarchist Thought
1 online resource
Keywords: This Handbook offers an authoritative, up-to-date introduction to the rich scholarly conversation about anarchy--about the possibility, dynamics, and appeal of social order without the state. Drawing on resources from philosophy, economics, law, history, politics, and religious studies, it is designed to deepen understanding of anarchy and the development of anarchist ideas at a time when those ideas have attracted increasing attention. The popular identification of anarchy with chaos makes sophisticated interpretations--which recognize anarchy as a kind of social order rather than an alternative to it--especially interesting. Strong, centralized governments have struggled to quell popular frustration even as doubts have continued to percolate about their legitimacy and long-term financial stability. Since the emergence of the modern state, concerns like these have driven scholars to wonder whether societies could flourish while abandoning monopolistic governance entirely. Standard treatments of political philosophy frequently assume the justifiability and desirability of states, focusing on such questions as, What is the best kind of state? and What laws and policies should states adopt?, without considering whether it is just or prudent for states to do anything at all. This Handbook encourages engagement with a provocative alternative that casts more conventional views in stark relief. Its30 chapters, written specifically for this volume by an international team of leading scholars, are organized into four main parts: I. Concept and SignificanceII. Figures and TraditionsIII. Legitimacy and OrderIV. Critiqueand Alternatives In addition, a comprehensive index makes the volume easy to navigate and an annotated bibliography points readers to the most promising avenues of future research.